Relation between gender,age and blood glucose level to successful rate of fibrinolytic therapy on patient with STEMI - Kintan Sari Nastiti; Ghitha Zahra Haifa; Yandi Ariffudin (ARKAVI [Arsip Kardiovaskular Indonesia), 2019)
Cardiovascular disease is a non communicable disease that caused more than 17 million death. 80% from all of the death is happened in low and middle earned country like Indonesia. This number make cardiovascular disease as a main cause of mortality in non communicable disease. Acute Coronary Syndrome is one of cardiovascular disease that oftenly happen on emergency room patient and STEMI is the most cases that happens a lot in emergency room. There are many factors that affect STEMI patients such as gender,age,smoking habit and hypertension. Reperfusion therapy like fibrinolytic have been a main choices to the doctors because of its fast outcome and easy procedure. This study to know the relation between sex,age and blood glucose level to successful rate of fibrinolytic therapy on patient with STEMI The research was conducted using cross sectional research design. The subjects of this research were 21 subjects whose taken from STEMI patient from emergency room of Gunung Jati hospital who took fibrinolytic therapy. The data is taken by secondary data from the patient’s medical record. Then, we are looking for related variable that concerned with this study. The result showed that there are no relation between gender,age and blood glucose level to successful rate of fibrinolytic therapy. There are no relation between gender,age and blood glucose level to successful rate of fibrinolytic therapy. The research result showed that p value is more than 0,05, which means that this result is has not a statistical meaning Keywords: STEMI, Fibrinolytic, Blood glucose, Gender, Age